2008
DOI: 10.1002/jnr.21743
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental abnormalities in neurosphere‐derived neural stem cells from SMN‐depleted mice

Abstract: Spinal muscular atrophy (SMA) is a genetic disorder caused by depletion of survival motor neuron (SMN) protein and characterized by degeneration of alpha-motor neurons in the spinal cord. We investigated the morphology and differentiation of neurosphere-derived neural stem cells (NSCs) generated from the brains of a hypomorphic series of SMA mice. Neurospheres from the Smn(-/-);SMN2 mice, which represent a model of very severe SMA, produced NSCs with increased proliferation during growth and differentiation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 29 publications
0
23
1
Order By: Relevance
“…SMA, a motoneuron developmental disorder, is caused by decrease in the amount of SMN protein [26, 27]. Intriguingly, we found the SMN reduced significantly along pMN differentiation, but expressed much higher in pMNs than GABA neurons.…”
Section: Discussionmentioning
confidence: 67%
“…SMA, a motoneuron developmental disorder, is caused by decrease in the amount of SMN protein [26, 27]. Intriguingly, we found the SMN reduced significantly along pMN differentiation, but expressed much higher in pMNs than GABA neurons.…”
Section: Discussionmentioning
confidence: 67%
“…Using cultured neurospheres from Smn-/-; SMN2 mice, Shafey and colleagues demonstrated that low Smn levels resulted in defects in neuronal differentiation and neuritogenesis [120]. Additional studies using in vitro models have shown that Smn accumulates in growth cones [121] and that reducing Smn levels leads to decreased axon outgrowth and growth cone size, attributable to defective beta-actin transport [122].…”
Section: The Contribution Of Developmental Pathways To Sma Pathogenesismentioning
confidence: 96%
“…Although SMA is often referred to as a motor neuron disease, recent evidence suggests that the splicing defects are present in multiple organs (Zhang et al 2008), and this can lead to diseaserelevant phenotypes in cells other than motor neurons (Hayhurst et al 2012). Surprisingly, neurospheres derived from the Smn À/À ;SMN2 mice, which represent a severe model of human SMA, did not differ in number when compared with wild type (Shafey et al 2008). Our data place PRMT5 upstream of SMN in the maturation cycle of Sm proteins in vivo.…”
Section: Role Of Prmt5 In Splicingmentioning
confidence: 99%